Single phase mixing in coiled tubes and coiled flow inverters in different flow regimes. (16th March 2017) - Sharma, Loveleen; Nigam, K.D.P.; Roy, Shantanu
Abstract: The present study focuses on the measurement of residence time distribution (RTD) in coiled tubes and coiled flow inverters (CFI) over a wide range of Reynolds numbers ( N Re ), in contrast to earlier studies that have reported the RTD over a very narrow range, mainly restricted to the laminar region. The analysis of our experimental data reveals the existence of three distinct flow regimes in coiled structures, viz. laminar flow with prominent Dean circulation, laminar flow with less contribution of Dean circulation, and fully developed turbulent flow. Even though the turbulent transition is known to be delayed in coiled geometries, good radial mixing brought in by Dean circulation results in a narrow RTD of the exiting fluid even when the flow is clearly laminar. For coiled flow inverters, the 90° inversion allows further enhanacement in overall mixing, albeit at the cost of extra pressure drop. The effect of different design parameters on the role of secondary flow for coiled geometries of varying number of inversions ( n ) and curvature ratios ( λ ) has been investigated. Finally, a master plot is developed between the dispersion number ( D / U d t ) and Reynolds number ( N Re ) showing the marked improvements in cross-sectional mixing in coiled flow, over that in straight tubes. Based on this, a correlation is presented. Highlights: Quantified radial mixing through coiled geometries on employing RTD measurements. The effect of 90° inversion on coiled geometries of "equivalent volumes" is judged. The role of coiled flow over a wide flow range ( 68 ≤ N Re ≤ 11146 ) shows three zones of performance. Proposed a generalized correlation to quantify mixing through coiled geometries. Presented "Master plot" for the intensity of axial dispersion as a function of N Re .